The Implementation of Tax Expenditures in Indonesian Tax Law: Evaluating Impacts on MSMEs and Economic Justice - Muhammad Rudy Aqbar; Hafizhah, Annisa; Ari Wijayanto (Universitas Sumatera Utara, 2025)
Tax expenditure policies, such as the 0.5% Final Income Tax rate stipulated by Government Regulation No. 23 of 2018, aim to foster the growth of Micro, Small, and Medium Enterprises (MSMEs) by reducing their tax burdens. These policies have shown positive impacts, particularly in improving tax compliance and alleviating the fiscal burden of MSMEs. However, challenges remain, including low tax literacy, bureaucratic complexities, and geographical disparities that hinder smaller and remote MSMEs from accessing these benefits. This paper examines how such policies align with human rights principles, such as the right to decent work and equitable economic access, while offering recommendations to ensure more inclusive implementation. By enhancing tax literacy, simplifying bureaucracy, and extending incentives to underserved MSMEs, tax expenditure policies can serve as an effective instrument to promote economic justice and sustainable development.